Non-pharmacological interventions for attention-deficit/hyperactivity disorder (ADHD) delivered in school settings: systematic reviews of quantitative and qualitative research. - Richardson, Michelle (Health Technol Assess, 2015)
BACKGROUND: Attention-deficit/hyperactivity disorder (ADHD) is a neurodevelopmental disorder characterised by age-inappropriate levels of inattention, impulsivity and hyperactivity. School can be particularly challenging for children with ADHD. Few reviews have considered non-pharmacological interventions in school settings. OBJECTIVES: To assess the effectiveness of non-pharmacological interventions delivered in school settings for pupils with, or at risk of, ADHD and to explore the factors that may enhance, or limit, their delivery. DATA SOURCES: Twenty electronic databases (including PsycINFO, MEDLINE, EMBASE, Education Resources Information Centre, The Cochrane Library and Education Research Complete) were searched from 1980 to February-August 2013. Three separate searches were conducted for four systematic reviews; they were supplemented with forward and backwards citation chasing, website searching, author recommendations and hand-searches of key journals. REVIEW METHODS: The systematic reviews focused on (1) the effectiveness of school-based interventions for children with or at risk of ADHD; (2) quantitative research that explores attitudes towards school-based non-pharmacological interventions for pupils with ADHD; (3) qualitative research investigating the attitudes and experiences of children, teachers, parents and others using ADHD interventions in school settings; and (4) qualitative research exploring the experience of ADHD in school among pupils, their parents and teachers more generally. Methods of synthesis included a random-effects meta-analysis, meta-regression and narrative synthesis for review 1, narrative synthesis for review 2 and meta-ethnography and thematic analysis for reviews 3 and 4. RESULTS: For review 1, 54 controlled trials met the inclusion criteria. For the 36 meta-analysed randomised controlled trials, beneficial effects (p < 0.05) were observed for several symptom and scholastic outcomes. Mean weighted effect sizes ranged from very small (d + < 0.20) to large (d + ≥ 0.80), but substantial heterogeneity in effect size estimates across studies was reported. Moderator analyses were not able to clarify which intervention features were linked with effectiveness. For review 2, 28 included studies revealed that educators' attitudes towards interventions ranged in positivity. Most interventions were rated positively or neutrally across different studies. The only intervention that consistently recorded positive attitudes from educators was daily report cards. For review 3, 33 studies met the inclusion criteria. Key findings included tensions regarding the preferred format of interventions, particularly how structured interventions were and the extent to which they are tailored to the child with ADHD. There were mixed views about the impact of interventions, although it was clear that interventions both influence and are influenced by the relationships held by children with ADHD and participants' attitudes towards school and ADHD. For review 4, 34 studies met the inclusion criteria. Key findings included the importance of causal attributions that teachers, parents and pupils made about ADHD symptoms, the decisions teachers made about treatment, the self-perceptions pupils developed about themselves, the role of the classroom environment and stigma in aggravating ADHD symptoms, and the significant barrier to treatment posed by the common presence of conflict in relationships between pupils-teachers, parents-teachers and pupils-peers in relation to ADHD. An overarching synthesis of the four reviews highlighted the importance of the context affecting interventions. It suggested that ADHD psychoeducation and relationship-building skills are potential implications for interventions. LIMITATIONS: The breadth of both interventions and outcomes in the reviewed studies presented a challenge for categorisation, analysis and interpretation in reviews 1-3. Across reviews, relatively few studies were conducted in the UK, limiting the applicability of findings to UK education. In reviews 1 and 2, the poor methodological quality of some included studies was identified as a barrier to establishing effectiveness or comparing attitudes. In review 3 the descriptive analysis used by the majority of studies constrained theorising during synthesis. Studies in review 4 lacked detail regarding important issues like gender, pupil maturity and school level. CONCLUSION: Findings suggest some beneficial effects of non-pharmacological interventions for ADHD used in school settings, but substantial heterogeneity in effect sizes was seen across studies. The qualitative reviews demonstrate the importance of the context in which interventions are used. Future work should consider more rigorous evaluation of interventions, as well as focus on what works, for whom and in which contexts. Gaps in current research present opportunities for the development and testing of standardised tools to describe interventions, agreement on gold-standard outcome measures assessing ADHD behaviour and testing a range of potential moderators alongside intervention trials. STUDY REGISTRATION: This study is registered as PROSPERO CRD42011001716. FUNDING: The National Institute for Health Research Health Technology Assessment programme.